Investigation of crack initiation path in AA7050-T7451 under fretting conditions. (April 2020) - Almeida, G.M.J.; Pessoa, G.C.V.; Cardoso, R.A.; Castro, F.C.; Araújo, J.A.
Abstract: Early crack orientation in 7050-T7451 aluminum alloy was investigated under fretting conditions. New tests were performed in the partial slip regime to observe the influence of the tangential load amplitude, mean bulk stress, and pad radius on the crack orientation. Three critical plane fatigue parameters were combined with different stress averaging methods to estimate the crack initiation direction. The normal stress-based Smith–Watson–Topper parameter provided better crack orientation estimates than the shear stress-based parameters. The experimental observations indicated a small increase in the early crack angle when the tangential load amplitude was raised. Highlights: Fretting crack initiation path was evaluated for AA7050-T7451. Critical Plane multiaxial fatigue criteria were used to estimate crack angle. The SWT parameter was more accurate predicting early crack orientation. Early fretting crack angles seem to increase when tangential load is raised.